Etnografia de uma escola Xikrin - Beltrame, Camila Boldrin (2013)
This dissertation presents an ethnographic study about a school of the Xikrin of the Bacaja, Mebengokré group (Gê), from southwest Pará, Brazil. It seeks to understand how the Xikrin have appropriated of this institution and its activities, what kind of reflections they have formulated about it and how they have inserted it in their daily lives. The school that the government offers to the Xikrin does not follow the principles of the Brazilian Constitution, which stipulate a differentiated and intercultural teaching to indigenous peoples based on the local specificities. During the fieldwork two movements were privileged. First, the daily activities of school have been monitored. That allowed the observation of the space in which the Xikrin children and non-Xikrin adults coexist and establish relations that were not observed in other moments in the village. The second movement was based on conversations with the men who explain what they consider a good school. In these situations the school is recognized as the place for children to learn the techniques and skills of the Whites. However, when they reach a certain maturity these knowledge are left aside so that the Xikrin knowledge begin to be demonstrated, as well as the relations they engender.